20dhw3 - Math 20D Solutions HW 3 Section 2.5 2 For this...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 20D Solutions: HW 3 Section 2.5 2. For this problem we do not need to solve the DE, only determine qualitative information about the solutions. We are given dy dt = ay + by 2 ,a > ,b > . To find equilibrium solutions, we set y = 0 = ay + by 2 and solve for y , getting y = 0 and y =- a/b as the solutions. Since a and b are both positive,- a/b is negative. So the plot of y with respect to y looks like an upward-opening parabola with zeros at- a/b and 0. In general for an autonomous equation, an equilibrium y = y is stable if y = f ( y ) is decreasing as it crosses the y axis at y , and unstable if it is increasing at y . Looking at the graph reveals that ay + by 2 decreasing at y =- a/b and increasing at y = 0, so- a/b is stable and 0 is unstable. With this information it is not hard to draw the phase line and qualitative plots of solutions. 7. a) To find equilibrium points we set y = 0 = k (1- y ) 2 . As long as k is nonzero, this equation has only one solution, y = 1. b) The plot of y = f ( y ) = k (1- y ) 2 is clearly going to be an upward opening parabola with a vertex at y = 1. (Since k > 0 it is upward opening.) If y 6 = 1, y is always positive. This means on either side of the equilibrium y = 1, solutions increase. In other words, a solution with initial value less than 1 will converge to the equilibrium, while a solution with initial value greater than 1 will diverge to ∞ . This is a so-called “semistable” equilibrium. c) This is a separable equation, so we rearrange and integrate: Z dy k (1- y ) 2 = Z dt. Using u-substitution with u = 1- y and integrating gives 1 k (1- y ) = t + C. The initial condition is y (0) = y , so solving for C gives C = 1 / ( k (1- y )). Now we must solve 1 k (1- y ) = t + 1 k (1- y ) for y . This is just algebra and we eventually get y = y + (1- y ) kt 1 + (1- y ) kt ....
View Full Document

{[ snackBarMessage ]}

Page1 / 3

20dhw3 - Math 20D Solutions HW 3 Section 2.5 2 For this...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online